Tourism Development Planning In Bantaeng District, South Sulawesi - Ridwan,; Yuliawan, Rahmat; Aly, M. Nilzam (International Journal of Psychosocial Rehabilitation, 2020)
Regional economic development is the result of the cooperation between the government and the community to improve a community’s welfare. The people who are still processing natural resources that are traditionally owned so that the natural resources become exportable and profitable goods, and it can also be enjoyed by the community to fulfill their daily needs. This is the impact of tourism development planning. This journal, as a concrete result of our research, is supported by the data obtained in Bantaeng District. This journal, which entitled "Tourism Development Planning in Bantaeng District, South Sulawesi" can be enjoyed by the people of Bantaeng District. The research method of this journal is qualitative method which in this case serves to answer and find solutions to problems. In this qualitative approach, researchers went directly to the field to examine the object of study and conducted direct interactions with the community intended to get in-depth information. The theoretical foundation used is planning development in tourism. From this research, it can be concluded that the planning apparatus that is used to carry out the planning activities has been working in accordance with applicable laws and regulations and considered as a breakthrough to prosper the people of Bantaeng District.